Pengaruh Adversity Quotient (AQ) dan Motivasi Berprestasi terhadap Prestasi Belajar Matematika - Nurhayati Nurhayati; Noram Fajrianti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
The study objective was to determine the effect of adversity quotient and achievement motivation of students to learn mathematics achievement. The method used in this study is a survey method. Analysis using multiple regression and correlation techniques. Sample size of 120 students obtained by random sampling technique. The instrument used was a questionnaire to measure the adversity quotient and achievement motivation, while performance is taken from the document teacher learning. Results of the hypothesis test, namely (1) a significant difference between adversity quotient and achievement motivation on mathematics achievement obtained (2) there is a significant relationship between adversity quotient on mathematics achievement and (3) there is a significant relationship between achievement motivation on achievement learn math